Urban development of Užice from the XV to the XVII century - Kuzović, Duško R. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The town of Užice had reached its highest progress in the period between the 14th and 17th centuries. Together with Belgrade and Sarajevo it became one of the three most important cities in the west Balkans. Turkish censuses testify about population trends in the colony, during the 15th and 16th century. In early 16th century, Užice was divided into a Muslim and a Christian part. In 1472. the town had 64 households organized in two mahalas. In 1567, Užice had grown to 634 households in 17 mahalas. The travelling notes of Haji Khalfa and Evliya Celebi mention Užice from the 17th century. Celebi noted that the town possesses 4800 houses, 1440 shops, 11 hans, 100 mills and 11 schools. Between 15th and 17th century town formed all the features of oriental settlement: irregular streets, functional division on residential mahalas and businnes center, mahalas organized around religious sites, and basic neighboorhood unit – mahala rather then street – organic form of transport network. In brief – a settlement that fully fits the cultural pattern of Muslims, not Christians. This work explores mentioned town from available lists.